Phylogenetic diversity and community structure of Planctomycetota from plant biomass-rich environments - Klimek, Dominika; Lage, Olga Maria; Calusinska, Magdalena (Frontiers in Microbiology, 2025)
Biomass-rich environments host diverse microbial communities that contribute to the degradation and recycling of organic matter. Understanding the community structure within these habitats is essential for elucidating the ecological roles and metabolic capacities of specific microbial groups. Here, we conducted an analysis of biomass-rich environments including diverse soil types, sediments, anaerobic digesters, termite guts, termite nests and other decaying biomasses, to explore the phylogenetic diversity and community structure of the Planctomycetota phylum, using short-read 16S rRNA gene amplicon sequencing. All sampled environments showed presence of Planctomycetota, with relative abundance ranging from nearly absent in animal manure to approximately 10% in soils. Across all samples, virtually 1,900 operational taxonomic units (OTUs) were identified, classified into diverse classes within Planctomycetota. Planctomycetotal phylogenetic diversity was highest in soils and sediments, while termite guts, exhibiting the lowest phylogenetic diversity, were dominated by a few core OTUs shared across different termite species. Notably, a single OTU, closely matching the 16S rRNA gene sequence of the Singulisphaera genus, was detected in all environments, though with relative abundance ranging from only a few reads to over 6% of the planctomycetotal community. Four environments such as soil, sediment, termite nest and decaying biomasses showed similar community structure with predominant genera such as Tepidisphaera, Telmatocola, and distantly related to Thermogutta, and Anatilimnicola. However, among these environments, weighted UniFrac analysis revealed that planctomycetotal communities in termite nests exhibited greater phylogenetic relatedness. Termite gut communities were the most divergent, followed by those in anaerobic digesters, where OTUs assigned to Anaerobaca and Anaerohalosphaera were the most abundant. Termite gut and phytoplankton bloom samples were dominated by OTUs affiliated with Pirellulales, suggesting their host-specific associations. Animal manure showed the presence of Planctomycetota, with 25% of detected OTUs not recognized by the SILVA database, possibly representing a novel, host-specific lineage distantly related to the Pirellulales order.